Apoiador matricial: uma possibilidade de promover a interdisciplinaridade entre profissionais da saúde - Cunha, Adeline Maria Castelo; Yasui, Silvio [UNESP] (My University, 2011)
This study aims to reflect the organization of the mental health services in primary care from a new organizational arrangement to health work, defined as Matrix Support (Campos, 1999), which aims to build technical and educational support in the relationship between health professionals from mental health professionals in the Family Health Strategy. The methodology used in the Matrix Support the “Wheel” method, which is mediated by a supporter who, through questions and reflections, points out possibilities for case discussions, promotes links between the health teams, discusses the concept of link between professionals and users, strengthens the co-responsability for the actions of health and tries to break the logic related with the services organized by referrals. So the wheels when they occur in health services enables the interdisciplinary, and through it, it is expected to talk about the complexity of the phenomena that surround each subject, so that they overcome the dichotomy between individual and collective, social and biological revealing new values to be incorporated into health practices. In front of this analysis that is theoric and conceptual, allied with the experience from a nursisn area professional that worked in this work method, can be concluded that this experience related here, eas strategic for the health care actions for strengthen based on the Unique Health system and Psych Rebuild principles.

Esse estudo tem como objetivo refletir sobre a organização das ações de Saúde Mental na Atenção Básica, a partir de um novo arranjo organizacional para o trabalho em saúde, definido como Apoio Matricial, o qual pretende construir suporte técnico-pedagógico, na relação entre profissionais da equipe de Saúde Mental junto aos profissionais da Estratégia Saúde da Família. O recurso metodológico utilizado no Apoio Matricial é a Técnica da Roda que é mediado por um apoiador que, por meio de questões e reflexões, aponta possibilidades para as discussões de casos, promove a articulação entre as equipes de saúde, discute o conceito de vínculo entre profissionais e usuários, fortalece a co-responsabilização pelas ações de saúde e tenta romper com a lógica dos serviços organizados por encaminhamentos. Assim, as rodas quando acontecem nos serviços de saúde possibilita a interdisciplinaridade, e, através dela, espera-se dialogar sobre a complexidade dos fenômenos que envolvem cada sujeito, de maneira que se superem as dicotomias entre o individual e o coletivo, o social e o biológico, revelando novos valores para serem incorporados às práticas de saúde. Diante da análise teórico-conceitual, aliada a experiência de uma profissional da área da enfermagem que atuou nessa modalidade de trabalho, conclui-se que essa experiência aqui relatada, foi estratégica para que as ações de cuidado em saúde fossem fortalecidas com base nos princípios do Sistema Único de Saúde e da Reforma Psiquiátrica.
Matrix support: a possibility to improve the interdisciplinarity between professionals and health
Keywords: Mental health; Primary care; Patient care team; Saúde mental; Atenção básica; Equipe interdisciplinar de saúde